In Diensten des Afrikanischen Sozialismus Tansania und die globale Entwicklungsarbeit der beiden deutschen Staaten, 1961-1990 - Burton, Eric (Studien zur Internationalen Geschichte, 2021)
Tanzania's efforts to construct an independent "African socialism" were part of a global discussion about the royal road to development, the ambiguous role of capitaist "developmental assistance," and the nature of "solidarity" with communist states. The study discusses negotiative processes and day-to-day experiences amid the global tensions of the Cold War, decolonization, and competing socialisms.